ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2021-2023 - Frasiska, Dea; Sucipto, Tia Novira; Nasution, M. Irsan (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2025)
Abstract This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk for the period of 2021-2023 using financial ratio analysis, wich includes liquidity, solvency, profitability, and activity ratios. The data analyzed ere obtained from thhe company’s annual financial statement and compared ith industy averages as benchmark. The result indicate that, overall, Indofood’s financial performance is in good condition. The company’s liquidity is very strong, as reflected by consistenly increasing current and quick ratios that exceed industry standards. Solvency has improved with declining debt-to-asset and debt-to-equity ratios, indicating a stable capital structure. Although profitability declined in 2022, the company recovered in 2023, achieving competitive profit levels. However, the company’s operational efficiency remains slightly below the industry average, as seen in the relatively low asset turnover ratio. Based on these findings, it is recommended that the company improve operational efficiency to optimize asset utilization, while maintaining a healthy capital structure and profitability level. Keyoword: Financial Statement Analysis, Liquidity, Solvency, Profitability, Activity. JEL Clasification : G32, M41, L25